Analysis of socioeconomic impacts due to the installation and operation of photovoltaic energy projects: review and analysis of interest level through a cognitive intelligence algorithm applied to TREND DAT (Research, Society and Development, 2023)
The photovoltaic energy sector has grown significantly in recent years as an alternative to clean energy production, but the implementation and operation of this energy matrix generate positive and negative socioeconomic impact. This article aims to analyze, through a cognitive and statistical intelligence algorithm, the degree of interest of people regarding the descriptors that portray the relevant socioeconomic implications associated with the installation of solar plants and the production of solar energy.   To this end, as a methodological procedure, two data search processes were used, both carried out through the Cafe tool of the CAPES platform. Through this search, the impacts were listed and five descriptors capable of synthesizing them were defined. Then, a cognitive intelligence algorithm was used to analyze the levels of interest, considering data from January 2010 to January 2020, extracted from TREND DATA databases, defining a score from 0 to 100 to classify certain descriptor in a certain period of time. The results were presented in two graphs, the first being a graph that shows the monthly rates of interest in the descriptors, and the second showing the average monthly level of interest for each descriptor. It is concluded that the most cited descriptors in disclosures of the digital media considered were the increase in job creation, the promotion of development and infrastructure and the increase in economic growth. On the other hand, the least cited by these disclosures werethe increase in land disputes and the increase in energy tariffs.